Autoimmune inflammatory reactions triggered by the COVID-19 genetic vaccines in terminally differentiated tissues - Panagis Polykretis; Alberto Donzelli; Janci C. Lindsay; David Wiseman; Anthony M. Kyriakopoulos; Michael Mörz; Paolo Bellavite; Masanori Fukushima; Stephanie Seneff; Peter A. McCullough (Taylor & Francis Group, 2023)
As a result of the spread of SARS-CoV-2, a global pandemic was declared. Indiscriminate COVID-19 vaccination has been extended to include age groups and naturally immune people with minimal danger of suffering serious complications due to COVID-19. Solid immuno-histopathological evidence demonstrates that the COVID-19 genetic vaccines can display a wide distribution within the body, affecting tissues that are terminally differentiated and far away from the injection site. These include the heart and brain, which may incur in situ production of spike protein eliciting a strong autoimmunological inflammatory response. Due to the fact that every human cell which synthesises non-self antigens, inevitably becomes the target of the immune system, and since the human body is not a strictly compartmentalised system, accurate pharmacokinetic and pharmacodynamic studies are needed in order to determine precisely which tissues can be harmed. Therefore, our article aims to draw the attention of the scientific and regulatory communities to the critical need for biodistribution studies for the genetic vaccines against COVID-19, as well as for rational harm-benefit assessments by age group.